Aplikasi Pembelajaran Pedosfer Berbasis Augmented Reality - Wildan; Khaerawati, Sri; Noval, Moh. (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The pedosphere is a combination of 2 words, namely the word pedo which means soil and sphera which means layer. The pedosphere is commonly referred to as the soil layer that is studied in high school. In this case, the researcher conducted research at SMA Negeri 5 Palu, which usually only used 2-dimensional images and theories in books to study the soil layers because of the lack of teaching aids. The purpose of this study is to help educators or students in the teaching and learning process recognize the soil layers by making an Augmented Reality (AR) technology application that can be used in all Android-based Smartphones. This application requires a marker to display a 3-dimensional object regarding the soil layer. The research method used by the researcher is the multimedia development method developed by Luther which is divided into 6 stages, namely concept, design, material collection, manufacture, testing and distribution. In the process of making the application, the researcher uses the Vuforia software as a marker database, Blender to create 3-dimensional objects and Unity as the application maker. The results of application testing on 47 respondents, namely 52% stated strongly agree, 36.2% agree, 10.5% quite agree, 1.1% disagree and 0.1% disagree.